Treatment of pediatric molluscum contagiosum with 10% potassium hydroxide solution. (June 2014) - Can, Burce; Topaloğlu, Filiz; Kavala, Mukaddes; Turkoglu, Zafer; Zindancı, Ilkin; Sudogan, Sibel
Background: Molluscum contagiosum (MC) is a common cutaneous viral infection of the skin that is frequently seen in children. Although lesions can resolve spontaneously, treatment is mandatory because of the psychological effect of widespread lesions in children. Potassium hydroxide (KOH) is a strong alkali that has been used by dermatologists for a long time in identifying the fungal infections from skin scrapings. Aims: We evaluated 40 children with MC for the safety and efficacy of treatment with topical 10% KOH aqueous solution. Methods: Parents were instructed to apply a 10% KOH aqueous solution, twice daily, with a cotton stick to all lesions. Treatment was continued till the lesions showed signs of inflammation or superficial ulceration. Assessments of response and side effects were performed at the end of week 2, week 4, week 8 and week 12. Results: We found complete clearance of lesions in 37 (92.5%) patients receiving topical 10%KOH solution after a mean period of four weeks. Three children dropped out of the study; two children reported severe stinging of the lesions and discontinued the treatment; the other patient developed hypopigmentation during the treatment. Local side effects were observed in 12 children (32.4%). Conclusion: Even though 10% KOH solution is associated with some local side effects, it is a safe, effective, inexpensive and noninvasive alternative treatment of MC in children.